Heat transfer performance of aluminium oxide nanofluids flow in a circular tube - Chiam, Huey Wen (2017)
Nanofluid is a stable mixture of nanoparticles with less than 100 nm which is dispersed into base fluids such as ethylene glycol (EG), water (W) and engine oil with relatively low thermal conductivity when compared with metal particles. The suspension of nanoparticles into base fluids is introduced as one of the passive methods to enhance thermal performance. The engineered coolant namely, the nanofluids are developed by various researchers with the aim to meet the challenges of improving the efficiency of cooling systems and subsequently, reduce the energy waste of the system. Consequently, this reduces the costs and emissions of greenhouse gases, which have become one of the major tasks for the industry. However, the study of forced convection heat transfer in different base mixtures is yet to be compared based on their performance under similar operating conditions. Therefore, this study endeavours to investigate the properties of Al2O3 (aluminium oxide) nanoparticles dispersed in different bases with volume ratios of 40:60, 50:50 and 60:40 (W:EG) and their ability in optimizing the performance of heat transfer in forced convection systems in circular pipes by simulation due to their properties such as high resistance for corrosion and wear with good thermal conductivity. In this research, the heat transfer performance of nanofluids is analyzed through a numerical method using the CFD (computational fluids dynamic) software. Initially, the Al2O3 nanofluids are formulated by the twostep method for volume concentrations of up to 2.0% at three different volume ratios of (W:EG). The thermo-physical properties of Al2O3 nanofluids namely, the thermal conductivity and viscosity are measured using the KD2 Pro thermal analyzer and Brookfield LVDV-III Ultra Rheometer respectively for a temperature range of 30 to 70 °C. The thermo-physical properties measurement of nanofluids is evaluated as part of the input parameters for the simulation work. The heat transfer coefficient, Nusselt number, friction factor and wall shear stress are collected by simulation using the realizable (k-ε) method to analyze the effects of volume concentration, working temperature and base volume ratio towards the heat transfer performance of Al2O3 nanofluids. The highest thermal conductivity enhancement of 12.6% were obtained at 2.0% volume concentration when compared to 50:50 (W:EG) base mixture. Whereas the highest viscosity enhancement of 248.8% were obtained at 2.0% volume concentration and 40:60 (W:EG) base mixture. The highest enhancement ratio for the heat transfer coefficient and the Nusselt number of Al2O3 nanofluids are 76.5% and 61.6% respectively at 60:40 (W:EG), 2.0% volume concentration and 30 °C. An enhancement ratio of 16.1 times is shown for wall shear stress for Al2O3 nanoparticles dispersed in 40:60 (W:EG) at 2.0% volume concentration and 70 °C. The Al2O3 nanofluids in 60:40 (W:EG) base fluid with 2.0% volume concentration have lower wall shear stress and higher heat transfer coefficient enhancement compared to 50:50 and 40:60 (W:EG) base nanofluids. Hence, it is recommended for various applications in the engineering field.